An e-VLBI image of SN1987A from Australian radio telescopes and the JIVE correlator - Tingay, Steven; Phillips, C.J.; Amy, S.W.; Tzioumis, A.K.; Kettenis, M.; Boven, E.P.; Szomoru, A.; Paragi, Z.; van Langevelde, H.; Verkouter, H.; Phillips, I.; Cowie, A.; et al. (Proceedings of Science, 2009)
We present an image of the expanding shell of the remnant associated with supernova1987A at the highest resolution to date at radio wavelengths, 85 milliarcseconds, using the e-VLBI technique, from 2007 October. This is comparable to the angular resolution obtainedwith the Hubble Space Telescope and is approximately 3 times higher than has been possiblewith the Australia Telescope Compact Array or 5 times higher than with the Chandra X-rayObservatory. The e-VLBI data at 1.4 GHz show good agreement with the ATCA data at 9GHz, resolving the substructure in the equatorial brightness enhancements of the remnant(allowing for the fact that the e-VLBI observations are sensitive to structure on angular scales<0.4?). We place a 3s upper limit on the time-averaged pulsar emission or a compact pulsarpowerednebula at this frequency of 1 mJy/beam. These observations were made usingtelescopes in Australia, with the data transferred in real-time to the European VLBI Networkcorrelator at the Joint Institute for VLBI in Europe, in The Netherlands, via high-speednetworks, as part of the EXPReS project, demonstrating the feasibility of a real-time global e-VLBI network at 512 Mbps per antenna.